"A translinear circuit for sinusoidal frequency division" - Abuelma’atti, M.T. (2005)
A translinear circuit for sinusoidal frequency division, by an integer number, is presented. The circua uses no inductors, no capacitors, no analog multipliers and is, therefore, attractive for integration. Simulation results are included.